GreatO+ Supplementation Leads to Greater Proportions of Omega-3 Fatty Acids in the Small Intestines of Holstein Steers - Ross L. Thorn; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:This study aimed to determine if supplementation of GreatO+, an extruded blend of flaxseed and microalgae (NBO3, Manhattan, KS), in Holstein steers would lead to greater amounts of fatty acids, particularly omega-3s, in the small intestines. Study Description:This study utilized 12 cannulated Holstein steers assigned to two treatments: with or without supplementation of GreatO+as a source of omega-3 fatty acids. Two periods were utilized, consisting of a 15-day adaptation interval and a four-day collection interval. After the end of the collection period, each steer was transitioned to the other treatment for the second period. This study was conducted at the Kansas State Intake Facility, equipped with automated feed and water troughs. The Bottom Line:Cattle supplemented with GreatO+have greater amounts of omega-3 fatty acid available for absorption in the small intestines.
Keywords: omega-3; ruminal biohydrogenation; flaxseed; microalgae